Digital Marketing in an Emerging Country: Exploratory Study of the Marketing Mix of SMES with Trust Seal - Gutierrez-Leefmans, Catalina (2016)
The study of digital marketing responds to technology changes as part of the digital economy. However, there is little scientific research of this subject in Mexican SMEs. This exploratory research aims to support the Mexican context knowledge through the observation to websites of SMEs with digital trust seal. The digital resources used as part of the marketing mix that can be observed externally in the websites were analyzed. The results showed that the most used resources were social networks, e-mail, those related to navigation ease and the variety of payment options. Nevertheless, other digital resources were underutilized. It was observed, in the SMEs studied, little attention in offering additional benefits and services to the product and low use of resources related to customer service. Despite showing a high interest in social networks, a quarter of the firms with a Facebook page did not give maintenance to it. It is concluded that Mexican SMEs are still at a basic stage in the use of digital resources in the marketing mix and that the marketing mix model is useful to observe the digital resources, but that some resources may belong to more than one element of the mix.